Estruturas narrativas na hipermídia: aplicações metodológicas para objetos educativos filosófico-religiósos - Neves, Miguel José das (2008)
The research performs an analysis of the methodologies used in digital productions, taking as a guide to methodological proposal of hypermedia as a tool for understanding the various forms of digital expression, applied to cases involving the philosophical knowledge (in reflective objects) with the forms of narrative in the Western tradition. Turning on the methodology hypermedia to the context of philosophical reflection and taking as paradigms, on the one hand, the digital production of the work O Mundo de Sophia and, the universe of games, model presented in Myst, this research reflects on the methodological structures necessary to consider a draft science of religion, back to medium and basic education, that takes into account the aspects of the digital language of hypermedia, They discussed authors who focus on the concepts that underpin the relationship between religion and the theme hypermedia, organizing and presenting the conceptual relations, from the constructivist theory of cognitive references. The use of hypermedia technology geared to the construction of knowledge is analyzed in the light of the proposal to implement the conceptual elements the biblical narrative to the digital world of cyberspace